(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, a heart sound signal is obtained from a stethoscope and converted into a wave pattern using a phonocardiograph (PCG). Various cardiac sound signal wave patterns obtained from PCG may have normal and abnormal sound signals. Abnormal sound signals are called heart murmurs. These sound signal wave patterns are to be made available in the form of a JPEG image which is in detecting heart abnormalities. Augmented Reality (AR) is a new technology in which computer-generated material such as graphics, text, audio, and objects are superimposed over a display screen to increase one’s view of the real-time world. The proposed framework is a mobile-based Android application that would work for all current and future versions of the operating system. In a marker-based augmented reality device, this approach allows the user to see the simulated object in the physical world. Image of the entity that is registered wave patterns of PCG signal could be provided by the consumer. The device is designed to detect the captured JPEG image pattern of the cardiac murmur signal and identify it using the hamming distance technique in this study. A new image pattern is formed as a result of the combination of the real world and generated objects, and it appears as if the real-world object and virtual object coexist within the environment. This is accomplished by the use of an Android-based handset. It is convenient and affordable since the consumer does not need to invest in costly and costly equipment such as an ECG machine, a treadmill, or an echo machine, among other options.